Social Isolation, Strain, and Youth Violence - Niño, Michael (Youth violence and juvenile justice, 2017)
This article examines the relationship between types of social isolation and violent delinquency. Deriving hypotheses from elements of general strain theory, we test whether the isolation-violence relationship varies across different types of isolated youth when compared to sociable youth. We also test whether other negative experiences and circumstances (types of social strain) associated with adolescence moderate the relationship between isolation types and violent delinquency. Using the National Longitudinal Study of Adolescent Health, we find that different types of social isolation had varying effects on violent delinquency. Socially disinterested youth show a greater capacity for violent behavior, but other types of marginalized youth showed no difference in violence when compared to sociable youth. Results also demonstrate that some types of strain moderate the isolation-violence relationship. The implications of these findings for research on peer relations, adolescent strain, and violence are discussed.